2014
DOI: 10.1155/2014/670186
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Methylene Blue Dye from Aqueous Solution Using Triton X-114 Surfactant

Abstract: In this study, the interaction energy between Triton X-114 surfactant + methylene blue or water and methylene blue + water was investigated using Hartree-Fock (HF) theory with 6-31G* basis set. The results of structures and interaction energies show that these complexes have good physical and chemical interactions at atom and molecular levels. However, the Triton X-114 surfactant + methylene blue complex shows stronger molecular interaction compared to other complexes systems. The order of the interaction ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…However, the excessively high temperature can also lead to the decomposition of analytes [ 35 ]. The increase of temperature will raise the viscosity of the surfactant-rich phase and result in a dilute problem with organic solvent [ 36 ]. Figure 7 a shows evidence where the recovery percentages of both triazine species increased from 30 to 50°C, while beyond 50°C, the recovery percentages decreased due to the increases of viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…However, the excessively high temperature can also lead to the decomposition of analytes [ 35 ]. The increase of temperature will raise the viscosity of the surfactant-rich phase and result in a dilute problem with organic solvent [ 36 ]. Figure 7 a shows evidence where the recovery percentages of both triazine species increased from 30 to 50°C, while beyond 50°C, the recovery percentages decreased due to the increases of viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…FV declines when the temperature rises, as at high temperatures, the interaction between the surfactant molecule and water decreases, which leads to the dehydration of the outer layers of the micellar aggregates, thus reducing the volume of the coacervate phase . Adsorption capacity of the dye in the surfactant depends strongly on the structure and strength of hydrogen bonding in the surfactant …”
Section: Dye–surfactant Interactions: Mechanismsmentioning
confidence: 99%
“…105 Adsorption capacity of the dye in the surfactant depends strongly on the structure and strength of hydrogen bonding in the surfactant. 108 Purkait et al 105 reported a convenient way of dye removal by the CPE method as well as recovering surfactant from the dilute phase. They achieved 100% removal of toxic Congo Red dye from wastewater.…”
Section: K Dmentioning
confidence: 99%
“…These results indicate high adsorption efficiency of the hydrogel H1 due to the electrostatic interaction between the dyes and the hydrogel H1 , while hydrogel H2 showed much higher adsorption efficiency. This observation can be rationalised by the presence of the large, polycyclic, aromatic residues which are embedded within the newly synthesised hydrogel which enables π–π stacking between the aromatic core of the polymer PePnUMA‐ co ‐AMPS and the dye molecules in a process that is augmented by H‐bonding 61–63 …”
Section: Resultsmentioning
confidence: 99%